The role of myelin oligodendrocyte glycoprotein in autoimmune demyelination: a target for multiple sclerosis therapy? - Lee, De-Hyung; Linker, Ralf (Expert Opinion on Therapeutic Targets, 2012)
INTRODUCTION: Myelin oligodendrocyte glycoprotein (MOG) is a myelin antigen at the outer surface of the central nervous system (CNS) myelin sheath, which may trigger T-cell as well as B-cell responses. It therefore constitutes a pivotal target for autoimmune responses, which result in inflammation and also demyelination in the CNS. In particular, it is a major target for auto-antibodies in experimental autoimmune encephalomyelitis (EAE), which mimics many aspects of multiple sclerosis (MS). B-cell responses toward MOG and anti-MOG antibodies have also been demonstrated in patients with demyelinating diseases, such as MS and acute disseminating encephalomyelitis (ADEM). Co-transfer of such anti-MOG antibodies in experimental models results in a distinct lesion pattern with antibody and complement-mediated demyelination, which is also hallmark of some lesion subtypes in MS. AREAS COVERED: A comprehensive literature search on MOG, B cells, MS, and ADEM was performed to outline the role of MOG in autoimmune demyelination in animal models and its relevance for human disease. EXPERT OPINION: Although the definite role of MOG in the pathogenesis of MS still remains to be clarified, innovative therapeutic strategies targeting B cells may reduce pathogenic immune responses against myelin auto-antigens including anti-myelin auto-antibodies.
EVALuna2:36327